2021
DOI: 10.1101/2021.01.15.426883
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Protein Phosphatase 1 regulates atypical mitotic and meiotic division inPlasmodiumsexual stages

Abstract: PP1 is a conserved eukaryotic serine/threonine phosphatase that regulates many aspects of mitosis and meiosis, often working in concert with other phosphatases, such as CDC14 and CDC25. The proliferative stages of the parasite life cycle include sexual development within the mosquito vector, with male gamete formation characterized by an atypical rapid mitosis, consisting of three rounds of DNA synthesis, successive spindle formation with clustered kinetochores, and a meiotic stage during zygote to ookinete de… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 84 publications
(111 reference statements)
1
2
0
Order By: Relevance
“…This phenotype of kinesin-13 depletion is different from that of the Δkinesin-20 , where apical polarity was not affected. A similar phenotype has been observed following knockdown of two P. berghei phosphatases, PPKL and PP1, where apical polarity was lost, affecting ookinete differentiation (49, 68).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…This phenotype of kinesin-13 depletion is different from that of the Δkinesin-20 , where apical polarity was not affected. A similar phenotype has been observed following knockdown of two P. berghei phosphatases, PPKL and PP1, where apical polarity was lost, affecting ookinete differentiation (49, 68).…”
Section: Discussionsupporting
confidence: 65%
“…A similar phenotype has been observed following the knockdown of two P . berghei phosphatases, PPKL and PP1, where apical polarity was lost, affecting ookinete differentiation (Guttery et al, 2012; Zeeshan et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Live-cell fluorescence microscopy has also been explored, with a recent study utilising lattice light-sheet microscopy to acquire 3D live time-lapse data of asexual P. falciparum invasion 26 . Other studies have reported the use of live-cell fluorescence imaging of microgametogenesis to define the phenotypes of transgenic P. berghei 27,28 cell lines.…”
Section: Introductionmentioning
confidence: 99%